Clinical and Radiological Characterization of an Infant with Caudal Regression Syndrome Type III - Kavinda Dayasiri; V. Thadchanamoorthy; Kaushika Thudugala; Aruni Ranaweera; N. Parthipan (Case Reports in Neurological Medicine)
Caudal regression syndrome is a rare disorder of developmental failure of lumbosacral vertebra and corresponding spinal cord during notochord formation. The severity varies from absent coccyx to complete absence of lumbosacral vertebra and caudal spinal cord. Both genetic and environmental factors are believed to play roles in aetiopathogenesis of caudal regression. The authors report a two-month-old child born to a diabetic mother, in whom the diagnosis of caudal regression syndrome type III was confirmed based on clinical and radiological characteristics. The child was managed by the multidisciplinary team to continue supportive care and screen and monitor for long-term complications. The long-term prognosis for mobility was less favourable given the presence of bilateral hip dysplasia and involvement of lumbar vertebra in addition to sacral agenesis.